UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENYAKIT MENULAR SEKSUAL (PMS) MELALUI METODE SNOWBALL THROWING DI KELAS XII. IPA.2 SMA NEGERI 1 RAMBAH TAHUN PELAJARAN 2021/2022 - Kisman Kisman (STKIP ROKANIA, 2022)
This study aims to improve student learning outcomes through the snowball throwing method. The basis of this research is the unsatisfactory student learning outcomes, meaning that there are still many below the KKM (65) that have not reached the expected target. This classroom action research was conducted in two cycles, consisting of planning, implementation, observation and reflection. The subjects in this study were students of class xii.ipa.2 SMA Negeri 1 Rambah. Techniques in data collection using tests and observations. The research instrument uses observation sheets and learning outcomes test questions. The results showed that before the implementation of the Snowball throwing method in physical education learning there were still many students who were under the KKM (65). After doing research on learning outcomes in cycle 1 meeting 1 obtained 86.0 and learning completeness reached 74.6% or there were 21 students out of 30 students who had finished studying. In cycle 2 increased by 82.2 and from 30 students who have completed as many as 26 students and 4 students have not achieved complete learning. So classically the complete learning that has been achieved is 96% (including the complete category).